AUTOMATION ANALYSIS OF SOFTWARE DEVELOPMENT STAGES (Modern information system and technologies, 2018)
An analysis of automation of software development stages with using intelligent systems. The use of intelligent systems in the stages of testing and applications implementing was analysed.